RADIATION-CURABLE INKS FOR FLEXOGRAPHIC AND SCREEN-PRINTING APPLICATIONS FROM MULTIFUNCTIONAL ACRYLATE OLIGOMERS - HAHN, LISA, MARIE; NARAYAN-SARATHY, SRIDEVI (2005)
The present invention relates generally to radiation-curable ink formulations, and particularly, but not by way of limitation, to a family of radiation-curable ink formulations specifically for flexographic and screen printing applications. The inventive ink formulations are based on multifunctional acrylate resins formed by the reaction of acrylate monomers and oligomers with ß-keto esters (e.g., acetoacetates), ß-diketones (e.g., 2, 4-pentanedione), ß-keto amides (e.g., acetoacetanilide, acetoacetamide), and/or other ß-dicarbonyl compounds that can participate in Michael addition reactions. L'invention concerne des formulations d'encre durcissable par rayonnement, et en particulier, mais non limité, une famille de formulations d'encre durcissable par rayonnement utilisée de manière spécifique dans des application de flexographie et de sérigraphie. Les formulations d'encre de l'invention sont à base de résines d'acrylate multifonctionnelles formées par la réaction de monomères et d'oligomères d'acrylate comprenant des esters de ss-cétone (par exemple de acétoacétates), de ss-dicétones (par exemple un 2, 4-pentanédione), des ss-céto amides (par exemple un acétoacétanilide, acétoacétamide), et/ou tout autre composé ss-dicarbonyle qui peuvent participer à la réaction de Michaël supplémentaire.